A study evaluation of tubal factors of infertility by hystero-salpingography and diagnostic laparoscopy - Devada, Kirti M.; Brahmbhatt, Jagruti K.; Jetani, Nirav J.; Modi, Dimpi M.; Chaudhari, Amit M.; Sharma, Suman S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Infertility is one of the commonest problems encountered in gynecology. Infertility appears to be a problem in 10-15% of Indian population. Tubal factors account for (20-40%) of infertility. The objective of the study was to demonstrate the role of hystero-salpingography and hystero-laparoscopy in evaluation of tubal factors for female infertility. Methods: Present study was carried out on 70 women attending the gynaecology OPD for investigation of infertility admitted between March 2014 to December 2014 in Gynecology ward, SSG Hospital attached to Government Medical College, Vadodara, Gujarat. Results: Out of 70 patients who underwent HSG tubal block was detected in 34 cases. Out of these 34 cases tubal block was detected only in 17 cases by laparoscopy and chromopertubation. One case which showed patent tubes on HSG had unilateral tubal block on chromopertubation test. Accordingly, sensitivity of HSG for tubal patency comes out to be 0.72, specificity of 0.94, positive predictive value of 97.43%, negative predictive value of 51.61%, positive likelihood ratio of 12.28 and negative likelihood ratio of 0.30. Conclusions: HSG being simple and less invasive technique along with higher specificity and lesser complications. Hystero-laparoscopy is a valuable technique for the complete assessment of female infertility.